2012
DOI: 10.4172/2161-0673.1000114
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption during Different Exercise Protocols in the Aged

Abstract: Objectives: The objective of this study was to compare response; specifically oxygen consumption; of a single bout of exercise using two different (constant and interval) intensity protocols in an aged population.Design: Ten males (68.8 ± 3.7 years) and six females (66.2 ± 3.5 years) were recruited for this study. All participants were actively involved in three hours of physical activity per week and were able to use a cycle ergometer unaided. Methods:Participants completed two randomised 20 min exercise prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…Analyzing the fatigue perception of the different training conducted, we found that the MICT presented a higher fatigue perception for HAP than in control participants. It seems that the short rest interval allowed the HAP to have a lower fatigue perception, a fact in line with previous studies that also found higher motivation in interval training than in continuous training [40]. It is also important to note that HAP presented more than twice CNS fatigue in MICT than control participants, but HIIT had almost the same fatigue perception in HAP as control patients.…”
Section: Discussionsupporting
confidence: 87%
“…Analyzing the fatigue perception of the different training conducted, we found that the MICT presented a higher fatigue perception for HAP than in control participants. It seems that the short rest interval allowed the HAP to have a lower fatigue perception, a fact in line with previous studies that also found higher motivation in interval training than in continuous training [40]. It is also important to note that HAP presented more than twice CNS fatigue in MICT than control participants, but HIIT had almost the same fatigue perception in HAP as control patients.…”
Section: Discussionsupporting
confidence: 87%